Testosterone, Gonadotropin, and Cortisol Secretion in Male Patients With Major Depression - Schweiger, Ulrich; Deuschle, Michael; Hamann-Weber, Bettina; Korner, Andreas; Lammers, Claas-Hinrich; Schmider, Jurgen; Gotthardt, Ulrike; Heuser, Isabella (Psychosomatic medicine, 1999)
Objective - Previous studies of sex hormone concentrations in depression yielded inconsistent results. However, the activation of the hypothalamic-pituitary-adrenal system seen in depression may negatively affect gonadal function at every level of regulation. The objective of this study was to explore whether major depressive episodes are indeed associated with an alteration of gonadal function. - Methods - Testosterone, pulsatile LH secretion, FSH, and cortisol were assessed using frequent sampling during a 24-hour period in 15 male inpatients with major depression of moderate to high severity and in 22 healthy comparison subjects (age range 22-85 years). - Results - An analysis of covariance model showed that after adjustment for age only, daytime testosterone (p < .01), nighttime testosterone (p < .05), and 24-hour mean testosterone secretion (p < .01) were significantly lower in the depressed male inpatients. There was also a trend for a decreased LH pulse frequency in the depressed patients (p < .08). - Conclusions - Gonadal function may be disturbed in men with a depressive episode of moderate to high severity.
Gesehen am 16.11.2020